Enhanced performance of nanostructured thin film anode through Pt plasma enhanced atomic layer deposition for low temperature solid oxide fuel cells. (20th November 2020) - Yu, Wonjong; Lee, Sanghoon; Ryu, Sangbong; Zheng, Chunhua; Cho, Gu Young; Cha, Suk Won
Abstract: Thin-film electrode deposited by sputtering has drawn attention due to high surface area and density of reaction sites for low-temperature solid oxide fuel cells. However, the nano-column structure of the sputtered film on the nanoporous anodic aluminum oxide (AAO) substrate has been showing low performances, possibly originated from low in-plane electrical connectivity and limited reaction area at electrolyte/electrode interface. We report here that application of 10 nm thickness of Pt plasma-enhanced atomic layer deposition (PEALD) on the nanoporous Ni-based anode and Gd doped ceria (GDC) deposited by sputtering dramatically enhances anodic reactions, significantly reduces ohmic and polarization resistances (25% reduction in ohmic, 50% reduction in polarization resistances), and improves the power density over 60% compared to the bare cells. It is noteworthy that Pt PEALD deposited on the nanoporous GDC layer shows much-improved performance compared to that deposited on the nanoporous anode structure. This is attributed to the enhanced contact area at Pt/GDC interface by exceptional conformal deposition of Pt PEALD and improved reaction sites from surface of GDC anode interlayer. Highlights: 10 nm-thick Pt PEALD was applied to the sputtered Ni-GDC anode. The peak power density of Pt PEALD cell was 60% higher than that of the reference. The enhanced contact area at Pt/GDC interface was attributed to Pt PEALD layer.